Application of Sediment Runoff Model to the Wlingi Reservoir Watershed, Indonesia - Rahman, Kurdianto Idi; Sisinggih, Dian; Asmaranto, Runi (Fakultas Teknik UB, 2020)
Sedimentation is the main problem in Wlingi reservoirs. They are suffering from severe watershed erosion and a heavy load of volcanic ash ejected from the eruption of Mount Kelud. Wlingi reservoir is significantly affected by recurrent volcanic activities of Mount Kelud. After the 2014 eruption, the capacity of Wlingi reservoirs decreased by 82.5% or only 3.70 million m3 from the initial capacity of 24 million m3. To analyze the impact of volcanic eruption disaster on reservoir sedimentation an integrated numerical model of sediment is required. The Fujiyama model is an integrated sediment runoff model using a basin model composed of unit channels and unit slopes. The model seems suitable for a mountainous basin. The simulation results from the model explain that the mechanism of transporting sediment into the Wlingi Reservoir can be explained based on the type of sediment transport. The movement of sediment originating from Kelud Mountain in Kali Lekso is strongly influenced by rainfall duration compared to the intensity of the rainfall. Also, the simulation model results explained that the mechanism of sediment transportation is dominated by suspended load or bed load which when large discharges will move with the mechanism of suspended load sediment transport.